2016
DOI: 10.1016/j.jtcvs.2015.11.041
|View full text |Cite
|
Sign up to set email alerts
|

The rise of new technologies for aortic valve stenosis: A comparison of sutureless and transcatheter aortic valve implantation

Abstract: SU-AVR is associated with better device success and a lower incidence of PVL, compared with TAVI. Nevertheless, patients treated with SU-AVR were more likely to receive a permanent pacemaker. SU-AVR and TAVI provide good results in patients who have severe symptomatic aortic valve stenosis. Given the multiple therapeutic options available, patients may receive the treatment that is most appropriate for their clinical and anatomical characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 40 publications
4
61
0
Order By: Relevance
“…When valve performance at rest is concerned, we observed similar results compared with other recently studies, either in terms of peak and mean gradients or in terms of EOA also when compared to a propensity‐matched cohort of patients undergoing TAVI . On the other hand, we observed slightly higher gradients in our multicenter European cohort of patients undergone AVR with Perceval sutureless bioprosthesis compared with a multicenter TAVI Italian experience (ITER registry) . Therefore, a hemodynamic comparison between Perceval sutureless bioprosthesis and TAVI is still a matter of concern and further studies are needed to confirm these results.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…When valve performance at rest is concerned, we observed similar results compared with other recently studies, either in terms of peak and mean gradients or in terms of EOA also when compared to a propensity‐matched cohort of patients undergoing TAVI . On the other hand, we observed slightly higher gradients in our multicenter European cohort of patients undergone AVR with Perceval sutureless bioprosthesis compared with a multicenter TAVI Italian experience (ITER registry) . Therefore, a hemodynamic comparison between Perceval sutureless bioprosthesis and TAVI is still a matter of concern and further studies are needed to confirm these results.…”
Section: Discussionsupporting
confidence: 87%
“…demonstrated that small size sutureless valve provided lowest gradients and larger EOA in an in vitro study, compared to two standard pericardial stented bioprostheses. These results have been confirmed clinically by Shresta et al., who observed a mean gradient of 13.6 ± 5.4 cm 2 and an EOA of 1.5 ± 0.25 cm 2 in a cohort of elderly patients with preoperative annulus ≤22 mm. Similarly, Dedeilias et al .…”
Section: Discussionsupporting
confidence: 73%
“…Moderate or greater PVL in TAVR has been associated with significant mortality , although notably none of our patients developed moderate or greater PVL postprocedurally. While new sutureless aortic valves offer larger effective orifice areas and lower rates of PVL , as future advancements are made in annular sealing technologies, the incidence of PVL after TAVR will likely decline.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, minimally invasive RDV-AVR could prove to be a significant competitor of TAVI, particularly in the high risk patients. In a recent multicenter propensity matched study comparing outcomes of 214 patients matched to either RDV-AVR or TAVI, there was no difference in 30-day or 1-year mortality, stroke, bleeding or myocardial infarction (73). However, the RDV-AVR patients had a higher procedural success rate and less incidence of paravalvular leaks at the cost of higher incidence of pacemaker insertion compared to the TAVI cohort.…”
Section: Sutureless Mini-avr In High Risk Patientsmentioning
confidence: 96%